Uji Efektivitas Ekstrak Biji Lamtoro (Leucaena leucocephala) sebagai Insektisida terhadap Kecoa Amerika (Periplaneta americana) - Adelia, Yuanda Wanda; Iskandar, Damayanti (Universitas Andalas, 2020)
Research on the effectiveness of lamtoro seeds (Leucaena leucocephala) extract has been carried out as an insecticide against American cockroaches (Periplaneta americana). The lamtoro seeds were extracted using maceration method with ethanol solvent, and obtained ethanol extract of lamtoro seeds. Lamtoro seeds extract was made in 5 concentrations of 0%, 2%, 6%, 10% and 14%. The effectiveness of the extract was tested using spray method with 10 adult cockroaches as a testing animal with 3 times repetition and observed for 72 hours. Observations have shown the decline in American cockroachesâ€™ activity is causing death. Mortality data were analyzed using probit analysis to determine LC50. The result of phytochemical test of lamtoro seeds extract are flavonoids, tannins and saponins. Lamtoro seeds extract was effective to kill American cockroaches, which percentage of mortality were 0%, 33%, 66%, 86% and 96% respectively at concentration 0%, 2%, 6%, 10%, and 14% with LC50 3,35%.Â